Diagnosis of childhood tuberculosis in Pakistan: Are national guidelines used by private healthcare providers? - Yaqoob, Aashifa; Hinderaker, Sven Gudmund; Fatima, Razia; Shewade, Hemant D.; Nisar, Nadia; Wali, Ahmed (International journal of infectious diseases, 2021)
•Evaluation of childhood tuberculosis (TB) diagnosis by private healthcare providers.•Highlighted low utilization of the national guidelines for childhood TB diagnosis.•Less than 50% of private healthcare providers followed the guidelines.•Better training and expansion of public-private partnerships could improve take-up. The National Tuberculosis Control Program (NTP) in Pakistan developed, with the Pakistan Paediatric Association, a pediatric scoring chart to aid diagnosis of childhood tuberculosis (TB). Our study compared the diagnostic practice of private healthcare providers in Pakistan with the NTP guidelines. A cross-sectional study comparing diagnosis of TB in children <15 years by Non-NTP private providers with the NTP’s pediatric scoring chart. A generalized linear model was used to determine the difference in adherence by Non-NTP private providers to the NTP guidelines for childhood TB diagnosis by associated factors. A total of 5193 (79.7% of presumptive childhood TB cases identified in the selected districts during the study) children were diagnosed with TB by Non-NTP private providers. A strong clinical suspicion of TB was present in 17.3%, and chest x-ray was suggestive of TB in 34.3%. The Kappa score between Non-NTP private providers and the NTP guidelines for diagnosing TB was 0.152. Only 47.8% of cases were diagnosed in line with the NTP guidelines. Children <5 years old with a history of TB contact had a higher chance of being diagnosed according to the NTP guidelines. This study indicates a low adherence of NTP guidelines for diagnosing childhood TB by private providers in Pakistan.